2022
DOI: 10.1190/geo2021-0058.1
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a low-cost direct current resistivity meter for humanitarian geophysics applications

Abstract: Insufficient access to safe drinking water is one of the most challenging global humanitarian issues. The development of low-cost microcontrollers and the widespread availability of cheap electronics components raise the possibility of developing and using low-cost geophysical instrumentation with open-source designs and software solutions to circumvent geophysical instrumentation capital cost issues. To these ends, we alter an existing low-cost DC resistivity meter design and develop an optional modular Raspb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…According to a study by R. Kumar et al (2016), high voltage and high current can help to overcome the limitations of low SNR and high RMS misfit in DC resistivity measurements. The authors found that increasing the current and voltage in the measurement system can improve the quality of the acquired data and reduce the uncertainty in the results (Sirota et al, 2022).…”
Section: Power Supplymentioning
confidence: 99%
“…According to a study by R. Kumar et al (2016), high voltage and high current can help to overcome the limitations of low SNR and high RMS misfit in DC resistivity measurements. The authors found that increasing the current and voltage in the measurement system can improve the quality of the acquired data and reduce the uncertainty in the results (Sirota et al, 2022).…”
Section: Power Supplymentioning
confidence: 99%
“…Direct-current resistivity is a surface geophysical method that can provide essential information for investigating subsurface geological structures by injecting electric current into the Earth and measuring the corresponding voltage. It can find applications in mineral resource exploration [1][2][3], environmental and urban geological surveys [4][5][6][7], and humanitarian geophysics [8]. Regular two-dimensional (2.5D) and three-dimensional (3D) surveys are now conducted.…”
Section: Introductionmentioning
confidence: 99%
“…This method entails measuring the electrical resistivity of various materials and structures beneath the surface by transmitting a direct current through the ground and assessing the resulting potential differences. Due to their environmentally friendly nature and cost-effectiveness, direct-current measurements have found extensive application in diverse fields, including engineering studies [1-4], hydro-geological work [5][6][7], mineral resource exploration [8,9], and humanitarian geophysics [10]. In these geophysical explorations, the topography is typically non-flat, and the presence of the terrain will lead to false anomalies in apparent resistivity [11].…”
Section: Introductionmentioning
confidence: 99%